Mechanisms of mitochondrial dysfunction and their impact on age-related macular degeneration - Kaarniranta, Kai; Uusitalo, Hannu; Blasiak, Janusz; Felszeghy, Szabolcs; Kannan, Ram; Kauppinen, Anu; Salminen, Antero; Sinha, Debasish; Ferrington, Deborah (Progress in retinal and eye research, 2020)
Oxidative stress-induced damage to the retinal pigment epithelium (RPE) is considered to be a key factor in age-related macular degeneration (AMD) pathology. RPE cells are constantly exposed to oxidative stress that may lead to the accumulation of damaged cellular proteins, lipids, nucleic acids, and cellular organelles, including mitochondria. The ubiquitin-proteasome and the lysosomal/autophagy pathways are the two major proteolytic systems to remove damaged proteins and organelles. There is increasing evidence that proteostasis is disturbed in RPE as evidenced by lysosomal lipofuscin and extracellular drusen accumulation in AMD. Nuclear factor-erythroid 2-related factor-2 (NFE2L2) and peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) are master transcription factors in the regulation of antioxidant enzymes, clearance systems, and biogenesis of mitochondria. The precise cause of RPE degeneration and the onset and progression of AMD are not fully understood. However, mitochondria dysfunction, increased reactive oxygen species (ROS) production, and mitochondrial DNA (mtDNA) damage are observed together with increased protein aggregation and inflammation in AMD. In contrast, functional mitochondria prevent RPE cells damage and suppress inflammation. Here, we will discuss the role of mitochondria in RPE degeneration and AMD pathology focused on mtDNA damage and repair, autophagy/mitophagy signaling, and regulation of inflammation. Mitochondria are putative therapeutic targets to prevent or treat AMD. •Mitochondria are key organelles in RPE degeneration.•Mitochondrial dysfunction is a hallmark of AMD.•Impairment of autophagy/mitophagy leads to increased protein aggregation in RPE.•NFE2L2 and PGC-1α signaling cascades protect RPE mitochondria.•Mitochondrial dysfunction evokes chronic RPE-derived inflammation.